2021
DOI: 10.3390/molecules26010223
|View full text |Cite
|
Sign up to set email alerts
|

The Maillard Reaction as Source of Meat Flavor Compounds in Dry Cured Meat Model Systems under Mild Temperature Conditions

Abstract: Flavor is amongst the major personal satisfaction indicators for meat products. The aroma of dry cured meat products is generated under specific conditions such as long ripening periods and mild temperatures. In these conditions, the contribution of Maillard reactions to the generation of the dry cured flavor is unknown. The main purpose of this study was to examine mild curing conditions such as temperature, pH and aw for the generation of volatile compounds responsible for the cured meat aroma in model syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Accordingly, the formation of alpha dicarbonyl products, which are maillard reaction products, can be expected more. Therefore, the curing method may have caused the formation of GO and MGO in pastırma (Li et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the formation of alpha dicarbonyl products, which are maillard reaction products, can be expected more. Therefore, the curing method may have caused the formation of GO and MGO in pastırma (Li et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The volume of media on each microplate well (Sartedt) was 200 μl and the volume of cell suspension 20 μl. Conditions tested were grouped into three stages of dry‐cured sausages processing, fermentative ( a w 0.97, salt 3%, pH 4.5), drying ( a w 0.93, salt 4%, pH 5) and final ( a w 0.87, salt 5%, pH 5.5) (Baldini et al, 2000; Corral et al, 2017; Li et al, 2021). The basal medium GPY was adjusted to the different stress conditions as above.…”
Section: Methodsmentioning
confidence: 99%
“…It might be due to the fact that although dry-aged meat contained a higher abundance of flavor precursors, the flavor volatiles might not be adequately generated during the cooking process to influence flavor perception. Previous studies found that the volatile generation from Maillard reaction is not only dependent on the concentration of the substrates but also on the environmental condition such as pH, water activity, and temperature [68,69]. Reports had also indicated that consumers rated higher for the flavor attribute when the pork product had a higher pH (>5.8) and was cooked to a lower degree of doneness [54,55], providing flavor descriptors such as sweet and less acidic [70], potentially due to greater volatile generation in the product.…”
Section: Metabolomics Analysismentioning
confidence: 99%
“…It was suggested that lower pH increases the presence of protonated amino groups, decreasing the reactivity during Maillard reaction and therefore influencing the final volatile concentration [71]. Additionally, the lower pH condition was also reported to decrease the presence of pyrazines, thiazoles, and furans volatiles, which have been known to contribute to the meaty and roasted flavors [14,69,72,73] often associated with dry-aged products. Similarly, changes in the water activity and cooking temperature have also been suggested to alter the rate and type of Maillard reaction in the product [71,74], impeding the volatile production during the cooking process.…”
Section: Metabolomics Analysismentioning
confidence: 99%